Punching shear strength of concrete slab with various corroded reinforcing bar - Loh, Wen Rong (2018)
Reinforced concrete is very commonly used in all building structures as it provides high relative strength, high toleration of tensile strain, improves ductility and good bond to the concrete. The disadvantage of reinforced concrete is corrosion might take place over time due to exposure to chloride ions. Which results in a decrease of tensile strength. Steel corrosion happens when the oxidation on anode and reduction on cathode happens at the same rate concurrently. Corrosion of reinforced concrete is a serious issue especially building located at the coastal area. Over the years, there had been different studies on the punching shear strength of normal and high strength reinforced concrete slabs. This report focuses on the punching shear strength of 10 Grade 40 concrete slab with various corroded reinforcement. However, there are only result of 2 non-corroded slabs in this report for the time being as corrosion of the other slabs takes quite a long time. Punching shear tests of 2 Grade 40 concrete slabs with various flexural reinforcement are presented. The dimensions of the slab are 2.2 × 2.2 × 0.15 m with a supporting column of 0.2 × 0.2 × 0.2 m. The purpose of the tests is to investigate if code equations (ACI 318) for punching shear overestimate the actual punching shear strengths of slabs that are provided with a low amount of flexural reinforcement or low reinforcement ratio.